2019
DOI: 10.1037/bul0000206
|View full text |Cite
|
Sign up to set email alerts
|

A meta-analysis of the emotional victim effect for female adult rape complainants: Does complainant distress influence credibility?

Abstract: Rape cases have a disproportionately high attrition rate and low conviction rate compared to other criminal offenses. Evaluations of a rape complainant's credibility often determine whether a case progresses through the criminal justice system. Even though emotional demeanor is not related to witness honesty or accuracy, distressed rape complainants are perceived to be more credible than complainants who present with controlled affect. To understand the extent and robustness of the influence of emotional demea… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(43 citation statements)
references
References 202 publications
(431 reference statements)
2
34
2
Order By: Relevance
“…Legal definitions of sexual harassment require that the potential victim experience either repeated harm over multiple instances or severe harm in one instance (EEOC, 2017). Moreover, perceived harm can shape judgments of credibility—victims who are perceived as more distressed are also perceived as more credible (Klippenstine & Schuller, 2012; Nitschke et al, 2019; Schuller et al, 2010). Perceived harm further plays an important role in punitive and legal judgments, such as shaping the level of punishment assigned to the perpetrator, as well as other judgments like the amount of compensation awarded to victims (EEOC, 2017; Vallano, 2013; van Doorn & Koster, 2019).…”
Section: Perceptions Of Sexual Harassmentmentioning
confidence: 99%
“…Legal definitions of sexual harassment require that the potential victim experience either repeated harm over multiple instances or severe harm in one instance (EEOC, 2017). Moreover, perceived harm can shape judgments of credibility—victims who are perceived as more distressed are also perceived as more credible (Klippenstine & Schuller, 2012; Nitschke et al, 2019; Schuller et al, 2010). Perceived harm further plays an important role in punitive and legal judgments, such as shaping the level of punishment assigned to the perpetrator, as well as other judgments like the amount of compensation awarded to victims (EEOC, 2017; Vallano, 2013; van Doorn & Koster, 2019).…”
Section: Perceptions Of Sexual Harassmentmentioning
confidence: 99%
“…In the same way that individuals are expected to convey a level of confidence that is congruent with the amount of information they possess, credible individuals are also expected to convey emotions that are congruent with the valence of the information they possess (Kaufmann et al, 2003;Nitschke et al, 2019). For example, Kaufmann et al (2003) found that mock jurors rated a rape victim as significantly more credible when she displayed negative emotions compared to when she displayed positive or neutral emotions.…”
Section: Source Credibilitymentioning
confidence: 98%
“…For Study 2, we had three preregistered predictions: H1: We expected that when participants read about a distressed complainant, they would evaluate her as more credible (and the defendant as more likely to be guilty) when they received the standard witness instructions from the judge compared with the trauma education instructions. We also expected that when participants viewed an unemotional complainant, they would evaluate her as less credible (and the defendant less guilty) when they received the standard witness instructions compared with the trauma education instructions (i.e., we expected to observe the emotional victim effect only when participants hear the standard witness instruction from the judge; Nitschke et al, 2019).…”
Section: Aim and Hypothesesmentioning
confidence: 99%
“…A disproportionately small number of rape cases result in conviction compared with other types of criminal offences, and jurors are less likely to convict the defendant when they perceive the complainant to lack credibility (e.g., Elkin, 2018; Ellison & Munro, 2010). Jurors expect that rape complainants should be distressed when they testify about the alleged rape in court (Ask, 2010) and perceive a distressed complainant to be more credible than an unemotional complainant (the emotional victim effect; Ask & Landström, 2010; Nitschke et al, 2019). This misleads the jury as rape complainants often show limited emotion when testifying because of trauma and a complainant's emotional state is not reliable to judge the complainant's credibility (e.g., Rothbaum et al, 1992).…”
Section: Barriers To Conviction In Rape Trialsmentioning
confidence: 99%